2020
DOI: 10.1111/cen.14274
|View full text |Cite
|
Sign up to set email alerts
|

Three years of growth hormone treatment in young adults with Prader‐Willi Syndrome previously treated with growth hormone in childhood: Effects on glucose homeostasis and metabolic syndrome

Abstract: Context Growth hormone (GH) has been approved for children with Prader‐Willi syndrome (PWS) and significantly improves body composition in adults with PWS. Adults with PWS are predisposed to develop impaired glucose tolerance (IGT) and diabetes mellitus type 2 (DMT2). Continuation of GH maintains body composition, but GH is known to induce insulin resistance, which might affect glucose homeostasis. Studies on long‐term effects of GH treatment in adults are very limited. Objective To investigate effects of 3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Unfortunately, this may not always be possible as growth hormone treatment is not available for all adults with PWS. Based on our data on the combined effect of growth hormone treatment and multidisciplinary care, supported by previously reported beneficial effects of GH treatment alone in both children and adults [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 68 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], we support the pledge by Hoybye et al for general approval of growth hormone treatment in adults with PWS [ 94 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unfortunately, this may not always be possible as growth hormone treatment is not available for all adults with PWS. Based on our data on the combined effect of growth hormone treatment and multidisciplinary care, supported by previously reported beneficial effects of GH treatment alone in both children and adults [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 68 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], we support the pledge by Hoybye et al for general approval of growth hormone treatment in adults with PWS [ 94 ].…”
Section: Discussionsupporting
confidence: 81%
“…In adults with PWS, GH treatment improves body composition (by increasing lean body mass and decreasing fat mass) and muscle strength, and decreases the prevalence of cardiovascular risk factors, even without proven GH deficiency. Furthermore, positive effects on endurance, several aspects of cognition, and quality of life have been reported [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Despite these beneficial effects, GH treatment is often not reimbursed by healthcare insurance for adults with PWS as GH deficiency cannot be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the majority of the included studies did not show impaired glucose tolerance with GH therapy; however, non‐significant increases in fasting glucose were recorded, but these all remained in the normal range. One group showed the progression of 3 patients from IGT to overt DM during GH therapy; however, this may be due to lifestyle factors, rather than GH therapy alone, 28,29 and a recent study, published after this systematic search, confirmed that fasting glucose and insulin levels remained stable after 3 years of GH therapy 52 . Höybye (2004) suggested that GH treatment should be combined with lifestyle changes and exercise, in order to reduce the negative outcomes on glucose tolerance 30 .…”
Section: Discussionmentioning
confidence: 97%
“…Although subjects with PWS seem to develop less frequent cardiovascular risk factors than subjects with simply obesity, some case reports of cardiovascular events have been reported mostly at a young age [ 72 , 89 ]. Although the milestone of the treatment of obesity in PWS is the prevention that could occur thanks to growth hormone (GH) therapy and lifestyle interventions started in childhood [ 32 ], nutritional interventions along with the use of current antiobesity drugs provide evidence to be effective in adult subjects with obesity [ 44 ]. Therefore, the current manuscript aims to provide an overview of the current evidence on obesity in PWS, starting from a physiopathological point of view to obesity-related complications and conservative management.…”
Section: Introductionmentioning
confidence: 99%